Curriculum and Syllabus for Teaching Arabic in General Secondary Schools (Evaluation Study) المنهج والمقرر لتعليم اللغة العربية فى المدارس الثانوية العامة (دراسة تقويمية) - Muhammad Syaifullah (JURNAL IJ-ATL, 2018)
One of the reasons for the delay of the Indonesian children in the educational process is that the cost of the school curricula taught by the conservation of materials. Research has shown that the educational process has been held in many grades and does not result in anything but insult and malaise. Therefore, this research aims to describe the curriculum and the curriculum for teaching Arabic in secondary school in Indonesia and evaluate its results.ومن أسباب تأخر أطفال إندونيسيا في العملية التعليمية هو أن تكلف المدارس بمناهجها التدريسية طلبتها بالحفظ للمواد الدراسية. وقد دلت الأبحاث على أن العملية التعليمية عقدت بكثير في الصف ولا ينتج منها إلا الشأمة والملالة. لذا، فإن هذا البحث يهدف إلى وصف المنهج والمقرر لتعليم اللغة العربية بالمدرسة الثانوية العامة في إندونيسيا وتقويم نتائجها.